Carfilzomib: A second-generation proteasome inhibitor for the treatment of multiple myeloma. (1st March 2015) - McBride, Ali; Klaus, Jeff O.; Stockerl-Goldstein, Keith
Abstract: Purpose: The pharmacology, clinical efficacy, safety, cost, dosage and administration, and place in therapy of carfilzomib for the treatment of multiple myeloma (MM) are reviewed. Summary: Proteasome inhibition in MM has become a cornerstone in treatment regimens. Carfilzomib, a second-generation proteasome inhibitor, has demonstrated efficacy in patients with relapsed or refractory disease who have received at least two prior therapies including bortezomib and an immunomodulatory agent. Carfilzomib is an irreversible inhibitor and binds to a different site than bortezomib on the proteasome. A Phase II study evaluated 266 heavily pretreated patients with relapsed or refractory MM who had received at least two prior therapies, including bortezomib and either thalidomide or lenalidomide. The overall response rate was 23.7%, with a median duration of response of 7.8 months. The median overall survival time was 15.6 months. Carfilzomib has a similar adverse-effect profile to bortezomib, including anemia, thrombocytopenia, fatigue, dyspnea, and nausea; however, it does not result in the development or worsening of peripheral neuropathy. Carfilzomib is infused intravenously over 2–10 minutes for 2 consecutive days every week for three out of four weeks, with a 12-day rest period. Dosing is based on the patient's actual body surface area. Carfilzomib is available in 60-mg vials for single infusion. The total cost for a year of therapy is approximately 155, 852. Conclusion: Carfilzomib, a second-generation proteasome inhibitor that irreversibly inhibits the 26S proteasome, has shown efficacy in clinical studies of patients with relapsed or refractory MM, though the drug's role in the management of MM is not yet clear.